Wybrane aspekty komunikacji terapeutycznej w kontekście kontaktu z pacjentem chorym psychicznie = Selected aspects of communication in the context of therapeutic contact with the patient mentally ill - Biegański, Piotr Paweł; Tudorowska, Malwina (Journal of Education, Health and Sport, 2016)
Biegański Piotr, Tudorowska Malwina. Wybrane aspekty komunikacji terapeutycznej w kontekście kontaktu z pacjentem chorym psychicznie = Selected aspects of communication in the context of therapeutic contact with the patient mentally ill. Journal of Education, Health and Sport. 2016;6(9):442-450. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.153864 http://ojs.ukw.edu.pl/index.php/johs/article/view/3855 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016. Wybrane aspekty komunikacji terapeutycznej w kontekście kontaktu z pacjentem chorym psychicznie Selected aspects of communication in the context of therapeutic contact with the patient mentally ill mgr Piotr Biegański Katedra Higieny, Epidemiologii i Ergonomii Zakład Ergonomii i Fizjologii Wysiłku Fizycznego Collegium Medicum w Bydgoszczy im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 85-094 Bydgoszcz, Curie Skłodowskiej 9 tel. (52) 585-36-15 e-mail: piotr.pawel.bieganski@gmail.com mgr Malwina Tudorowska Katedra Pielęgniarstwa Zachowawczego Zakład Pielęgniarstwa Psychiatrycznego Collegium Medicum w Bydgoszczy im. Ludwika Rydygiera w Bydgoszczy UMK w Toruniu 85-821 Bydgoszcz, ul. Łukasiewicza 1 tel.: (52) 585-58-22/fax.: (52) 585-58-49 e-mail: malwina.tudorowska@gmail.com Streszczenie: Komunikacja terapeutyczna jako część procesu porozumiewania się pomiędzy pacjentem a personelem medycznym jest istotnym elementem leczenia począwszy od diagnozy. Celem całego procesu jest wzmocnienie sfery psychicznej ze względu na różnorodność przebiegu choroby. Wsparcie terapeuty poprzez odpowiednie komunikowanie się nie jest procesem psychoterapeutycznym a reakcją na stan chorobowy pacjenta i jego sytuację życiową. Czynnikami wzmacniającymi tego typu komunikację są nawiązanie dobrych relacji oraz wprowadzenie interwencji terapeutycznych. Porozumiewanie się z pacjentem chorym psychicznie wymaga szczególnego zaangażowania poprzez otwartość, zrozumienie, akceptację. Należy minimalizować bariery wynikające z uwarunkowań fizycznych, społecznych tak aby budować zaufanie pacjenta tak aby proces komunikacji był jak najbardziej efektywny. Słowa kluczowe: komunikacja, komunikacja terapeutyczna, choroba psychiczna Abstrakt: Therapeutic communication as part of the process of communication between the patient and the medical staff is an important element of treatment from diagnosis. The aim of the whole process is to strengthen the psychiatric due to the variety of the disease. Support therapist through appropriate communication is not a psychotherapeutic method but a reaction to the condition of the patient and his life situation. Factors reinforcing this type of communication is to establish good relations and the introduction of therapeutic interventions. Communication with the patient mentally ill requires special commitment through openness, understanding, acceptance. We should minimize the barriers stemming from the conditions of physical, social, in order to build the confidence of the patient so that the process of communication as effective as possible. Key words: communication, therapeutic communication, mental illness